MEASURING CUSTOMER SATISFACTION: A LITERATURE REVIEW - Nadia Angraini; Rahmi Fahmy; Hafiz Rahman; Ma'ruf Ma'ruf (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
Customer satisfaction is interesting to study because it is one of the most important factors for businesses to increase their income. This research examined earlier research on customer satisfaction. This research focused on collecting information from references in international articles and summarizing it to find the dominant point in the research that had been conducted earlier. The reviewed data were from Elsevier and Emerald Publishers. In total, 55 articles were reviewed. The purpose of this research was to know which model was dominantly used in the reviewed articles, which software had aided researchers in the past, and which software was predominantly used. This research could assist researchers and businessmen in doing research that focuses on customer satisfaction, thus helping them obtain the desired references to examine customer satisfaction.